Sistem Informasi Akuntansi Manajemen, Pengendalian Manajemen terhadap Kinerja Manajerial dengan Variabel Moderating Teknologi Informasi - Suprantiningrum Suprantiningrum; Aurora Diskayani Lukas (Politeknik Ganesha Medan, 2021)
The success of garment companies in increasing business competition is influenced by good managerial performance. Managers to achieve optimal performance in planning, control and decision making need the support of management accounting information systems, management control systems and information technology. This study aims to determine the effect of management accounting information systems and management control systems on managerial performance, the effect of management accounting information systems and management control systems on managerial performance with information technology as a moderating variable. The research object is the manager of a garment company in the city of Semarang with a population of 200, sampling using probability sampling, the sample used is 67 managers, determining the number of samples using the Slovin formula. The data used are primary data, data collection using a questionnaire with 5 Likert scale. The data analysis used in this research is validity test, reliability test, multiple linear regression and interaction regression. The results showed that the management accounting information system had a significant positive effect on managerial performance. The management control system has a significant positive effect on managerial performance. Information technology is a moderating variable on the effect of management accounting information systems and management control systems on managerial performance, meaning that information technology strengthens the influence of management accounting information systems and management control systems on managerial performance in garment companies in the city of Semarang.